Cardiac tumorgenic potential of induced pluripotent stem cells in an immunocompetent host with myocardial infarction. (March 2011) - Ahmed, Rafeeq PH; Ashraf, Muhammad; Buccini, Stephanie; Shujia, Jiang; Haider, Husnain Kh
Aim: Genetic reprogramming of somatic cells with stemness genes to restore their pluripotent status is being studied extensively to generate pluripotent stem cells as an alternative to embryonic stem cells. This study was designed to examine the effectiveness of skeletal myoblast-derived induced pluripotent stem cells (SkiPS) from young male Oct4/GFP transgenic mice for regeneration of the infarcted heart.Methods & results: A mouse model of permanent coronary artery ligation was developed in young female immunocompetent C57BL/6J or C57BL/6x129S4 SV/jae Oct4/GFP mice. SkiPS labeled with Q-dots (3 ×× 10 5 in 10 µµl basal Dulbecco''s modiﬁed Eagle''s medium) were transplanted in and around the area of infarct immediately after coronary artery ligation (n = 16) under direct vision. Control mice (n = 12) were injected with the same number of skeletal myoblasts. Histological studies documented successful engraftment of SkiPS in all the surviving animals 4 weeks later. However, six of the 16 SkiPS-transplanted (37.5%) animal hearts showed intramural teratomas, whereas no tumor growth was observed in the control mice. Q-dot-labeled donor cells were also observed at the site of tumors. Histological studies revealed that teratomas were composed of cells from all of the three embryonic germ layers. Ultra-structure studies confirmed the histological findings and showed regions with well-organized myofibrillar structures in the tumors.Conclusion: Undifferentiated induced pluripotent stem cells should not be recommended for cardiac transplantation unless screened for specific teratogenic precursors or predifferentiated into cardiac lineage prior to transplantation.